FIQH ECOLOGY-BASED GREEN BANKING FRAMEWORK: A MODEL FOR ENVIRONMENTALLY FRIENDLY CORPORATE SOCIAL RESPONSIBILITY - Amiruddin, Muhammad Majdy; Qaed, Issa; Husain, Saddan (Tadayun: Jurnal Hukum Ekonomi Syariah, 2024)
This research aimed to develop a Green Banking framework based on the principles of Fiqh Ecology, implemented through CSR initiatives in Indonesian sharia banking. A qualitative methodology was employed, including literature review and policy analysis tools, along with coding analysis to discern primary themes from collected data. Regulations and policies related to environmental protection in the banking sector, such as Law No. 7 of 1992 on Banking (amended by Law No. 10 of 1998), Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH), Bank Indonesia Regulation No. 7/2/PBI/2005, Bank Indonesia Circular Letter No. 7/3/DPNP, and green financing regulations, align with the principles of Fiqh Ecology in Sharia banking. The integration of Fiqh Ecology and corporate social responsibility (CSR) into the Green Banking framework has produced significant outcomes. The principles of Fiqh Ecology—Balance (Mizan), Responsibility (Amanah), Prohibition of Destruction (Fasad fil Ardh), Maintenance (Hifz), and Sustainability (Istidamah)—are reflected in the CSR policies of Islamic banking. These policies include initiatives such as environmental risk assessments in credit decisions, creating green financial products, funding policies for eco-friendly projects, annual carbon footprint reporting, collaboration with NGOs, investment in renewable energy, and public campaigns. Abstrak Penelitian ini bertujuan mengembangkan kerangka Perbankan Hijau berdasarkan prinsip-prinsip Fikih Ekologi dan diimplementasikan melalui inisiatif CSR di perbankan syariah Indonesia. Metodologi yang digunakan adalah kualitatif, meliputi tinjauan literatur dan alat analisis kebijakan, serta analisis kode untuk mengidentifikasi tema utama dari data yang dikumpulkan. Regulasi dan kebijakan terkait perlindungan lingkungan di sektor perbankan, seperti UU No. 7 Tahun 1992 tentang Perbankan (diubah oleh UU No. 10 Tahun 1998), UU No. 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup (UUPPLH), Peraturan Bank Indonesia No. 7/2/PBI/2005, Surat Edaran Bank Indonesia No. 7/3/DPNP, serta regulasi pembiayaan hijau, sejalan dengan prinsip Fikih Ekologi dalam konteks perbankan syariah. Penggabungan Fikih Ekologi dan corporate social responsibility (CSR) dalam kerangka Perbankan Hijau menghasilkan hasil yang signifikan. Prinsip Fikih Ekologi, yaitu Keseimbangan (Mizan), Tanggung Jawab (Amanah), Larangan Pengrusakan (Fasad fil Ardh), Pemeliharaan (Hifz), dan Keberlanjutan (Istidamah), tercermin dalam kebijakan CSR perbankan syariah. Kebijakan ini mencakup inisiatif seperti penilaian risiko lingkungan dalam keputusan kredit, penciptaan produk keuangan hijau, kebijakan pendanaan proyek ramah lingkungan, pelaporan jejak karbon tahunan, kerja sama dengan LSM, investasi dalam energi terbarukan, dan kampanye publik.